Biocoagulant from biomass for water treatment - Foo, Vernon Yee H'ng (2024)
The escalating demand for sustainable and environmentally friendly water treatment solutions has sparked interest in exploring alternative coagulants derived from natural sources. This study investigates the efficacy of biomass extracted from Annona seeds as a biocoagulant for treating turbidity in wastewater. The effectiveness of the Annona seed biomass is compared against alum and ferric chloride through various operating conditions such as turbidity removal efficiency and dosage requirements. Additionally, the study examines the influence of operating conditions such as pH, mixing intensity, and stirring duration on the coagulation process. Annona seed will be grinded into powder, sieved through a 2mm wire mesh, and left to dry overnight before mixing with distilled water. The concentration of all three coagulants will be modified to 1000mg/L to treat wastewater with a dosage of 30mL. Moreover, the kaolin wastewater will have a concentration of 100mg/L, and a working volume of 300mL is used throughout the study. The initial and final turbidity of wastewater will be measured in the testing, whereas the turbidity reduction efficiency will be calculated using the given formula. The research shows that all the coagulants struggle to fully perform when the wastewater is under high pH. When the pH value of wastewater reaches 11, the turbidity reduction of alum, Annona seed, and ferric chloride dropped to 11.09%, 13.01%, and 7.89%, respectively. This is because the coagulants are less effective at neutralizing the charges on particles at higher pH, resulting in reduced aggregation and poorer coagulation efficiency. Additionally, the turbidity reduction rate of all three coagulants performs better when the mixing time during fast-mixing processes is longer. The turbidity reduction rate of alum, Annona seed, and ferric chloride increases to 66.17%, 59.35%, and 51.55% when the high-speed mixing duration is at 40 minutes. For wastewater treatment under different mixing speeds, the turbidity reduction rate increases when the speed of the initial mixing process increases. The turbidity reduction rate of alum, Annona, and ferric chloride elevated to 50.55%, 45.77%, and 21.47%, respectively, at high-speed mixing of 250rpm for 15 minutes followed by slow-mixing speed of 40rpm for 30 minutes.